The balanced unsaturated fatty acid supplement constituted by woody edible oils improved lipid metabolism and gut microbiota in high-fat diet mice - Chen, Xi; Ran, Jingqi; Mazhar, Muhammad; Zhu, Yong; Lin, Yichen; Qin, Likang; Miao, Song (Frontiers in Nutrition, 2023)
The dietary intervention has demonstrated effectiveness in improving hyperlipidemia and obesity. Woody edible oils are rich in unsaturated fatty acids (UFAs) that could positively affect lipid metabolism. In this study, the blended oil (BLO), a balanced UFA supplement, constituted by Zanthoxylum bungeanum (Chinese Red Pepper) seed oil, walnut (Juglans regia) oil, camellia (Camema oleifera) seed oil and perilla (Perilla frutescens) seed oil was established referring to the Chinese dietary reference intakes, in which the ratios of monounsaturated/polyunsaturated fatty acids and ω-6/ω-3 polyunsaturated fatty acids were 1:1 and 4:1, respectively. The BLO was administrated to KM mice fed a high-fat diet (HFD) by gavage every day at a dose of 3.0 mL/kg·bw for ten weeks to assess its effects on serum lipid levels, liver antioxidant activities and gut microbial composition. The results showed that the BLO improved hepatic steatosis, liver oxidative stress, and serum lipid levels. Additionally, there was an increased abundance of Lactobacillus, Allobaculum, and Blautia, along with a decreased abundance of Staphylococcus in cecal contents. These changes were found to be positively correlated with the metabolic improvements, as indicated by Spearman's correlation analysis. These findings implied the practicality of the balanced unsaturated fatty acid consumption in preventing hyperlipidemia and obesity.